No change in viral set point or CD4 cell decline among antiretroviral treatment‐naïve, HIV‐1‐infected individuals enrolled in the Danish HIV Cohort Study in 1995–2010. Issue 6 (21st February 2013) - Helleberg, M; Kronborg, G; Larsen, CS; Pedersen, G; Pedersen, C; Obel, N; Gerstoft, J
<x xml:space="preserve">Abstract</x> Objectives Recent studies have reported faster progression of HIV infection than anticipated based on results from earlier studies. The aim of the present study was to examine if the virulence of HIV‐1 infection changed in the period 1995–2010 among chronically HIV‐infected individuals in Denmark. Methods We included all patients registered in the Danish HIV Cohort Study, who were diagnosed in 1995–2009, had a CD4 count > 100 cells/μL at diagnosis and had at least two CD4 measurements prior to initiation of antiretroviral therapy (ART). Changes in viral set point and rate of CD4 cell decline from enrolment until the initiation of ART by calendar year of HIV diagnosis were analysed. Time to first CD4 count < 350 cells/μL was compared among patients diagnosed in 1995–2000, 2001–2005 and 2006–2010. Results We followed 1469 HIV‐infected patients for a total of 5783 person‐years. The median viral set point was 4.27 log10 HIV‐1 RNA copies/mL [interquartile range (IQR) 3.58–4.73 log10 copies/mL]. The median CD4 cell decline per year was 57 cells/μL (IQR 10–139 cells/μL). In analyses adjusted for age, gender, origin, route of transmission and CD4 count at diagnosis, there were no associations between year of diagnosis and viral set point or CD4 cell decline. Time to first CD4 count < 350 cells/μL did not change in the study period [incidence rate ratio (IRR) 0.90 (95% confidence interval (CI) 0.76–1.06) for 2001–2005 and 1.09 (95% CI 0.79–1.34) for 2006–2010 compared with 1995–2000]. Conclusions We found no evidence of changing trends in viral set point, CD4 cell decline or time to CD4 count < 350 cells/μL during the period 1995–2010 in a cohort of chronically HIV‐infected individuals.